Financial Reporting Integrity in the Digital and Sustainability Era: A Systematic Literature Review on Governance, ESG, and Technological Transparency - Winda Wulandari; Sri Widyastuti; Harnovinsah Harnovinsah; Dwi Prastowo (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Digital transformation, sustainability demands, and evolving governance standards have challenged financial reporting integrity. However, existing studies have largely examined governance, ESG disclosure, and digital technologies separately, resulting in fragmented perspectives that limit a comprehensive understanding of their interrelationships. Objective: This study systematically reviews and synthesizes research on financial reporting integrity by examining how sustainability pressures, digital transformation, and governance mechanisms converge to reshape transparency and accountability in corporate reporting. Methods: A Systematic Literature Review (SLR) guided by the PRISMA 2020 guidelines was conducted. Data were sourced from the Scopus database and covered publications from 2021 to 2025. Following rigorous inclusion and exclusion screening procedures, 28 peer-reviewed articles were selected from an initial pool of 713 records. The TCCM Framework (Theory, Context, Characteristics, and Methodology) was applied to classify, evaluate, and synthesize the research findings. Results: Agency Theory and quantitative research methods dominate the field. Recent studies increasingly emphasize ESG disclosure, blockchain technology, and artificial intelligence (AI) as key determinants of transparency. Significant research gaps remain regarding cross-disciplinary approaches, emerging market contexts, and ethical risk assessments in digital reporting practices. This review reconceptualizes financial reporting integrity as a multidimensional socio-technical governance phenomenon shaped by governance accountability, sustainability legitimacy, and technological transparency. Conclusion: Future research should adopt interdisciplinary, mixed-method, and cross-country research frameworks to investigate greenwashing mechanisms, digital reporting ethics, and the interplay between emerging regulatory frameworks, including the International Sustainability Standards Board (ISSB) Standards and IFRS Sustainability Disclosure Standards, and technological transformation within sustainability-oriented reporting environments.